Identification of individual prokaryotic cells by using enzyme-labeled, rRNA-targeted oligonucleotide probes. - Amann, R I (1992)
A method to microscopically detect and identify individual cells of members of the domains Bacteria and Archaea is presented. rRNA-targeted oligonucleotides were 5' end labeled with the enzyme horseradish peroxidase and used for whole-cell hybridization. Specifically bound probe was visualized by the enzymatic formation of an intracellular precipitate from the substrate diaminobenzidine. Permeation of the enzyme-labeled probe into whole fixed cells of gram-negative bacteria required their pretreatment with lysozyme-EDTA, whereas permeability of some archaebacterial cells was improved by addition of detergent to the hybridization buffer. Hitherto we had not achieved penetration of enzyme-labeled probe into gram-positive bacteria and yeast cells. This method should be a valuable tool for identification of suitable prokaryotic cells in environments with elevated background fluorescence or in situations in which an epifluorescence microscope is not available.